Assessment of Monocyte Chemo-Attractant Protein-1 (MCP-1) and Other Biochemical Parameters in Iraqi Pregnant Women - Ali, Israa T.; Haddad, Namir I. A.; Hussein, Ekhlas A. (Iraqi Journal of Science, 2022)
The monocyte chemo-attractant protein-1 (MCP-1) is one of the pro-inflammatory cytokines. It controls the passage and infiltration of monocytes, macrophages, natural killers, and T cells into the sites of inflammation. The aim of this study is to inspect the role of MCP-1 in maternal metabolic, physiological changes and pregnancy complications like gestational diabetes mellitus, dyslipidemia, and hypertension to develop pharmaceutical strategies for these complications. This study included ninety Iraqi women divided into three groups: thirty pregnant women in their first trimester as the P1 group; thirty pregnant women in their third trimester as the P2 group; and thirty healthy non-pregnant women as the control or C group. Serum concentrations of MCP-1 were analyzed by the ELISA technique (sandwich principle). Fasting plasma glucose (FPG), C-reactive protein (CRP), fasting serum insulin (FSI), glycosylated hemoglobin (HbA1c), lipid profile, systolic, diastolic blood pressure, liver function enzymes ALT, AST and anthropometric parameters were measured. Our results revealed that serum MCP-1 significantly declined in the first trimester (P1) compared to the C group (p<0.05) and non-significantly declined in the third trimester (P2) compared to that in the C group, while there was a significant difference in serum MCP-1 between the P1 and P2 groups (p<0.05 ). Serum CRP showed a highly significant increase in the P1 and P2 groups compared to the C group at (p<0.01). There is a highly significant difference between the P1 and P2 groups (p<0.01). Serum MCP-1 had a significant positive correlation with body mass index (BMI), body fat percentage (BF %), systolic blood pressure (SBP) and C-reactive protein (CRP) in the P2 group (p<0.05). No significant differences in FPG or HbA1C were found between all the studied groups. Lipid parameters: TC, TG, LDL, and VLDL showed a highly significant increase in the P2 group compared to the C and P1 groups (p<0.01). HDL showed a highly significant decrease in the P2 group compared to the C group (p<0.01), while it was only significantly decreased in the P2 group compared to the P1 group (p<0.05). Depending on these results, we found that serum MCP-1 declines in pregnancy, the BMI, BF%, and the contractile arterial blood pressure (SBP) have a positive correlation with MCP-1 in late pregnancy, and the inflammation marker (CRP) has an independent association with MCP-1 in early gestation.